CHARACTERISTIC OF AREA-BASED PLACEMENT OF SUBJECTS OF SMALL ENTITIES IN THE AGRO-INDUSTRIAL COMPLEX OF THE VOLGOGRAD REGION - Mariya S. Lata (Статистика и экономика)
The characteristic of placement of subjects of small entities is presented in the article depending on soil and climatic zones of rural territories of the Volgograd region. As a result of the carried-out monitoring of rural municipal areas features of specialization, concentration of agricultural production and a problem of subjects of small entities in agrarian sector of economy of the Volgograd region were revealed.